Site-oriented conjugation of poly(2-methacryloyloxyethyl phosphorylcholine) for enhanced brain delivery of antibody - Ren, Jie; Jepson, Chloe E.; Nealy, Sarah L.; Kuhlmann, Charles J.; Osuka, Satoru; Azolibe, Stella Uloma; Blucas, Madison T.; Nagaoka-Kamata, Yoshiko; Kharlampieva, Eugenia; Kamata, Masakazu (Frontiers in Cell and Developmental Biology, 2023)
Antibody therapeutics are limited in treating brain diseases due to poor blood-brain barrier (BBB) penetration. We have discovered that poly 2-methacryloyloxyethyl phosphorylcholine (PMPC), a biocompatible polymer, effectively facilitates BBB penetration via receptor-mediated transcytosis and have developed a PMPC-shell-based platform for brain delivery of therapeutic antibodies, termed nanocapsule. Yet, the platform results in functional loss of antibodies due to epitope masking by the PMPC polymer network, which necessitates the incorporation of a targeting moiety and degradable crosslinker to enable on-site antibody release. In this study, we developed a novel platform based on site-oriented conjugation of PMPC to the antibody, allowing it to maintain key functionalities of the original antibody. With an optimized PMPC chain length, the PMPC-antibody conjugate exhibited enhanced brain delivery while retaining epitope recognition, cellular internalization, and antibody-dependent cellular phagocytic activity. This simple formula incorporates only the antibody and PMPC without requiring additional components, thereby addressing the issues of the nanocapsule platform and paving the way for PMPC-based brain delivery strategies for antibodies.